LC8/DYNLL1 is a 53BP1 effector and regulates checkpoint activation. Issue 12 (15th April 2019) - West, Kirk L; Kelliher, Jessica L; Xu, Zhanzhan; An, Liwei; Reed, Megan R; Eoff, Robert L; Wang, Jiadong; Huen, Michael S Y; Leung, Justin W C
Abstract: The tumor suppressor protein 53BP1 plays key roles in response to DNA double-strand breaks (DSBs) by serving as a master scaffold at the damaged chromatin. Current evidence indicates that 53BP1 assembles a cohort of DNA damage response (DDR) factors to distinctly execute its repertoire of DSB responses, including checkpoint activation and non-homologous end joining (NHEJ) repair. Here, we have uncovered LC8 (a.k.a. DYNLL1) as an important 53BP1 effector. We found that LC8 accumulates at laser-induced DNA damage tracks in a 53BP1-dependent manner and requires the canonical H2AX-MDC1-RNF8-RNF168 signal transduction cascade. Accordingly, genetic inactivation of LC8 or its interaction with 53BP1 resulted in checkpoint defects. Importantly, loss of LC8 alleviated the hypersensitivity of BRCA1-depleted cells to ionizing radiation and PARP inhibition, highlighting the 53BP1-LC8 module in counteracting BRCA1-dependent functions in the DDR. Together, these data establish LC8 as an important mediator of a subset of 53BP1-dependent DSB responses.